Membangun Demokrasi Dan Good Local Governance Melalui Pilkada Langsung - Anwaruddin, Awang (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2005)
The first direct election for the head and vice-head of local government in Indonesia—or Pilkada Langsung—was successfully started in the Kutai Kertanegara regency at the beginning of June 2005. The same election will be held immediately by 225 provinces, regencies and cities all over the country. It is too early to say that other elections will gain the same succes as different areas in Indonesia perform different characteristics. The tigh competition coloring the election may also trigger the conflicts among the supporters of the candidates. However, we hope that the spirit to enhance democracy and to develope good local governance through the direct election will be able to eliminate the facing contraints. The discussion developed in this paper will cover the legality and mechanism of the election, efforts to enhance democracy and good local governance that will result in the recommendation to achieve a succesfull direct election.